Chasing Cassandra - Kleypas, Lisa (Kleypas, Lisa. Ravenels., 2020)
Railway magnate Tom Severin is wealthy and powerful enough to satisfy any desire as soon as it arises. Anything- or anyone- is his for the asking. It should be simple to find the perfect wife- and from his first glimpse of Lady Cassandra Ravenel, he<U+2019>s determined to have her. But the beautiful and quick-witted Cassandra is equally determined to marry for love- the one thing he can<U+2019>t give. Severin is the most compelling and attractive man Cassandra has ever met, even if his heart is frozen. But she has no interest in living in the fast-paced world of a ruthless man who always plays to win. When a newfound enemy nearly destroys Cassandra<U+2019>s reputation, Severin seizes the opportunity he<U+2019>s been waiting for. As always, he gets what he wants- or does he? There<U+2019>s one lesson Tom Severin has yet to learn from his new bride: Never underestimate a Ravenel. The chase for Cassandra<U+2019>s hand may be over. But the chase for her heart has only just begun . . .